2004
DOI: 10.2172/15007924
|View full text |Cite
|
Sign up to set email alerts
|

Disposition Options for Hanford Site K-Basin Spent Nuclear Fuel Sludge

Abstract: This report provides summary-level information about a group of options that have been identified for the disposition of spent-nuclear-fuel sludge in the K-Basins at the Hanford Site. This study builds upon a review performed in CY1999 which established the current baseline for sludge retrieval and storage from K Basin. (a) Building upon this study, an expert review team was assembled to consider expert knowledge and project progress which has evolved since that time. The membership of this team is provided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Because H 2 is flammable, its release into the gas phase above K Basin sludge during sludge storage, processing, immobilization, shipment, and disposal is a concern to the safety of those operations in the current alternatives and design development activities of the K Basin Sludge Treatment Project (STP). Previous considerations of the disposal of the K Basin sludge to the Waste Isolation Pilot Plant (WIPP) determined that the sludge amount that could be loaded into drums for shipment as remote-handled transuranic waste was limited by the H 2 generation rate (Mellinger et al 2004). The evaluations showed that the H 2 generation rate is dominated by the H 2 arising from the uranium-water reaction with much lower contributions from radiolytic H 2 .…”
Section: Uranium Metal Reaction With Water and Means To Decrease H 2 mentioning
confidence: 99%
“…Because H 2 is flammable, its release into the gas phase above K Basin sludge during sludge storage, processing, immobilization, shipment, and disposal is a concern to the safety of those operations in the current alternatives and design development activities of the K Basin Sludge Treatment Project (STP). Previous considerations of the disposal of the K Basin sludge to the Waste Isolation Pilot Plant (WIPP) determined that the sludge amount that could be loaded into drums for shipment as remote-handled transuranic waste was limited by the H 2 generation rate (Mellinger et al 2004). The evaluations showed that the H 2 generation rate is dominated by the H 2 arising from the uranium-water reaction with much lower contributions from radiolytic H 2 .…”
Section: Uranium Metal Reaction With Water and Means To Decrease H 2 mentioning
confidence: 99%
“…A technology assessment (Mellinger et al 2004) concluded that to meet the WIPP hydrogen gas concentration criterion, both a uranium metal removal operation and some reduction of the reaction rate by a solidification matrix will be required. Accordingly, testing is required to establish the technical feasibility of segregation processes and to determine the extent to which the uranium metal can be removed.…”
Section: Decision and Testing Objectivesmentioning
confidence: 99%
“…), and a preconceptual process flow diagram ( Figure A.1). Based on discussions with vendor technical staff and mineral processing experts, it was concluded that gravity mineral concentration technology potentially could remove 85% or more of the uranium metal from the bulk of the K Basin sludge (Mellinger et al 2004). Removing 90% of uranium metal from design-basis KE floor sludge would likely satisfy a conservative interpretation (a) of the WIPP hydrogen generation limit.…”
Section: Decision and Testing Objectivesmentioning
confidence: 99%
“…Pulses are used mainly for echo location, while tones are related to social contexts and communication. Tones, also commonly called "whistles", are produced in the range of 300Hz-24 kHz [1,3]. With their high dependence on sound, research in bioacoustics becomes fundamental for unraveling the influence of anthropogenic activities on their environment and vocal behavior [1,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%